Excavating sponges from the Pacific of Central America, descriptions and a faunistic record - Pacheco, C.; Carballo, J.L.; Cortés, J.; Segovia, J.; Trejo, A. (Zootaxa, 2018)
Excavating sponges are one of the main groups of bioeroders in coral reefs. Their diversity has been thoroughly studied in some regions: in the Caribbean, the Mediterranean, and the Indo-Pacific, including the Mexican Pacific. However, there is a lack of information from the Pacific of Central America, with only a few records from Panama and Costa Rica. This study provides additional distributional records and taxonomic descriptions of species collected between 2011 and 2016 at nine localities along the Pacific coast of El Salvador, Nicaragua, Costa Rica and Panama. A total of fourteen species of excavating sponges from three orders, three families, and five genera are considered valid in this area. Nine are new records for Central America, six are new records for El Salvador, three are new records for Nicaragua and eleven are new records for Costa Rica. The species collected from Panama were already recorded before. The species here described are Cliona amplicavata, Cliona californiana, Cliona euryphylle, Cliona microstrongylata, Cliona aff. mucronata, Cliona pocillopora, Cliona tropicalis, Cliona vermifera, Cliothosa tylostrongylata, Pione cf. carpenteri, Pione mazatlanensis, Thoosa calpulli, Thoosa mismalolli and Siphonodictyon crypticum. We also reviewed the literature related to excavating sponges from Central America, and the taxonomic status of respective species was updated. We provide a faunistic record of 14 excavating sponge species for Central America. Our data are expected to be useful for management and conservation purposes.